Performance and Carcass Characteristics of Broiler Finishers Fed Acidifier Based Diets - Ogunwole, O.A.; Abu, O.A.; Adepoju, I.A. (Pakistan Journal of Nutrition, 2011)
Effects of supplementing diets with Biotronics SE (an acidifier) in replacement of Oxytetracycline-HCl (Antibiotic Growth Promoter) (AGP) on performance and carcass characteristics of broiler chickens was investigated using 128 Marshall Strain day old broilers. The birds were randomly allotted to four treatments with each treatment made of a duplicate of 16 chicks per replicate. Four isocaloric and isonitrogenous diets (A: control diet without Oxytetracycline-HCl and Biotronics SE®; Diet B had 0.1% Oxytetracycline-HCl only, Diet C contained 0.3% Biotronics SE® only while Diet D contained 0.1% Oxytetracycline HCl and 0.3% Biotronics SE®) were formulated and each diet was offered in mash form to their respective birds from day 21 until week 7. At day 49, four chickens from each replicate were selected and sacrificed for the determination of carcass characteristics. Weight gain and feed intake were significantly higher (p<0.05) for birds on dietary treatment D. Variations in values obtained for the final body weight and mortality indices were however similar (p>0.05). Biotronics supplementation significantly improved (p<0.05) feed conversion ratio, live weight gain and bled weight. Other carcass and internal organs weights were not significantly (p>0.05) affected by the inclusion of AGP or acidifier in the diets. Biotronics SE can suitably replace AGP in broilers diets.